Pendampingan Graha Steam Kelurahan Bandarharjo Semarang dengan Pemanfaatan Teknologi Tepat Guna Aplikasi Steam.Mulasi - Agnita Siska Pramasdyahsari; Rina Dwi Setyawati; Yuris Setyoadi; Putri Setyowati; Delina Putri; Muhammad Nur Cahya (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Graha STEAM assistance through Appropriate Technology (TTG): The Steam.mulation application aims to support the learning achievements of school-age youth who have lost their enthusiasm for learning as a result of the Covid-19 pandemic. This community service activity is carried out to help children develop 21st century learning skills such as critical thinking and problem solving, creative thinking, collaboration and communication (4C) by mentoring STEAM learning activities and implementing TTG using an Android-based application Steam.mulation. Data on TTG users' responses to improving 4C capabilities was collected by distributing questionnaires to Graha STEAM mentoring participants. The questionnaire included 11 main questions about the application and its perceived benefits. Participants had installed and used the steam application prior to completing the questionnaire. Respondents filled out the questionnaire based on their current situation. The mentoring questionnaire, which was administered using the TTG Steam.mulation application, received a very positive response. Overall, the response provided is excellent and has the potential to improve 4C capabilities